Eurocentrism as a function of capitalism: a critique based on the categorial-logic of the marxist theory of dependency - Peto, Lucas Carvalho [UNESP] (Ariadna Ediciones & Saint Petersburg State Univ, 2022)
The objective is to present a critique of Eurocentrism as a specific and necessary function of capitalism. This criticism is twofold and addresses: a) the expropriation imposed on Latin American countries by European countries during the historical development of capitalism and b) indeterminate analysis that do not present the dynamics that make it necessary to place the Eurocentrism function in the development process capital as a mode of production for itself. The logic that underlies this hypothesis is based on Marx's writings and on the marxist theory of dependency.
Keywords: Marxist Theory of Dependency; Capitalism; Eurocentrism; Latin America; Economic History